Theory of Auditing: Evaluation, Investigation, and Judgment (Book). - Dennis, David K.; Burns, Thomas J. (The Accounting Review, 1980)
Reviews the book "Theory of Auditing: Evaluation, Investigation, and Judgment," by Charles W. Schandl.